Acteoside From Ligustrum robustum (Roxb.) Blume Ameliorates Lipid Metabolism and Synthesis in a HepG2 Cell Model of Lipid Accumulation - Sun, Le; Yu, Fan; Yi, Fan; Xu, Lijia; Jiang, Baoping; Le, Liang; Xiao, Peigen (Frontiers in Pharmacology, 2019)
We aimed to ascertain the mechanism underlying the influence of Acteoside (ACT) from Ligustrum robustum (Roxb.) Blume on lipid metabolism and synthesis. ACT, a water-soluble phenylpropanoid glycoside, is the most abundant and major active component of Ligustrum robustum, and the leaves of Ligustrum robustum, known as kudingcha (bitter tea), have long been used as an herbal tea for weight loss in China. Recently, based on previous work, our team reached a preliminary conclusion that phenylpropanoid glycosides in Ligustrum robustum most likely contribute greatly to lowering lipids, but its mechanism is not very clear. Here, we conducted in silico screening of currently known phenylethanoid glycosides from Ligustrum robustum and attempted to explore the hypolipidemic mechanism of ACT, the representative component of phenylethanoid glycosides in Ligustrum robustum, by RNA-seq technology and quantitative real-time PCR (qPCR). First, the screening results of 6 compounds were docked with 15 human source protein targets, and 3 of 15 protein targets were related to cardiovascular diseases. Based on previous experimental data and docking results, we selected ACT, which had positive effects for further research. We generated a lipid accumulation model of HepG2 cells treated with a high concentration of oleic acid and then extracted RNA after administering 50 μmol/L ACT for 24 hr. Subsequently, we performed transcriptomic analysis of the RNA-seq results, which revealed a large number of differentially expressed genes. Finally, we randomly selected some genes for further validation by qPCR; the results agreed with the RNA-seq results and confirmed their reliability. In conclusion, our experiments proved that ACT of L. robustum can ameliorate lipid metabolism and synthesis by regulating the expression of multiple genes, including Scarb1, Scarb2, Srebf1, Dhcr7, Acat2, Hmgcr, Fdft1 and Lss, involving several pathways, such as the glycolytic, AMPK, and fatty acid degradation pathways, etc..